Математичне та комп'ютерне моделювання оптимізаційних задач розміщення тривимірних об'єктів (за матеріалами наукового повідомлення на засіданні Президії НАН України 11 березня 2020 р.) - Чугай, А.М. (Вісник НАН України, 2020)
Дослідження присвячено розв'язанню оптимізаційних задач упаковки тривимірних тіл шляхом побудови точних математичних моделей та розроблення підходів, основаних на застосуванні оптимізаційних методів нелінійного програмування і сучасних розв'язувачів. Розроблено конструктивні засоби математичного та комп'ютерного моделювання відношень орієнтованих та неорієнтованих тривимірних тіл, поверхня яких утворена циліндричними, конічними, сферичними поверхнями та площинами, у вигляді нових класів вільних від радикалів Ф-функцій та квазі-Ф-функцій. Побудовано і досліджено базову математичну модель задачі оптимальної упаковки тривимірних тіл, поверхня яких утворена циліндричними, конічними, сферичними поверхнями і площинами, та різні її реалізації, які охоплюють широкий клас наукових і прикладних задач упаковки тривимірних тіл. Розроблено загальну методологію розв'язання задач упаковки тривимірних тіл, що допускають одночасно неперервні повороти та трансляції. Запропоновано стратегії, методи і алгоритми розв'язання оптимізаційних задач упаковки тривимірних тіл з урахуванням технологічних обмежень. The research is devoted to the solution of optimization problems of packing three-dimensional bodies by construction exact mathematical models and developing approaches based on the use of optimization methods of non-linear programming and modern solvers. Constructive tools of mathematical modeling and computer modeling of the relationship between oriented and non-oriented three-dimensional bodies which boundary is formed by cylindrical, conical, spherical surfaces and planes in the form of new classes of free of radicals Ф-functions and quasi-Ф-functions are developed. Based on the tools of mathematical modeling the basic mathematical model of the problem of optimal packing of three-dimensional bodies whose boundary is formed by cylindrical, conical, spherical surfaces and planes is constructed and investigated. Also various implementations that cover a wide class of scientific and applied problems of packing three-dimensional bodies are constructed. A general methodology for solving the problems of packing three-dimensional bodies that simultaneously allow continuous rotations and translations are developed. Strategies, methods and algorithms for solving optimization problems of packing three-dimensional bodies with account for technological constraints (minimum permissible distances, prohibition zones, the possibility of continuous translations and rotations) are proposed. Based on the proposed tools of mathematical modeling, mathematical models, methods and algorithms, software using parallel computing technology for automatically solving the optimization problems of packing three-dimensional bodies is created. The results obtained can be used to solve problems of optimization of layout solutions, computer modeling in materials science, powder metallurgy and nanotechnologies, optimization of the 3D printing process for SLS additive production technology, and in information and logistics systems that optimize transportation and storage of goods.